Anticancer and Immunomodulatory Effects of Lactobacillus plantarum LS/07, Inulin and Melatonin in NMU-induced Rat Model of Breast Cancer - Kassayová, Monika; Bobrov, Nikita; Strojný, Ladislav; Orendáš, Peter; Demečková, Vlasta; Jendželovský, Rastislav; Kubatka, Peter; Kisková, Terézia; Kružliak, Peter; Adamkov, Marián; Bomba, Alojz; Fedoročko, Peter (Anticancer research, 2016)
BACKGROUND/AIM: Chemopreventive activity of a new probiotic strain Lactobacillus plantarum LS/07 (PRO) and prebiotic oligofructose-enriched inulin (PRE) in rat mammary carcinogenesis induced by procarcinogen 7,12-dimethylbenz[a]anthracene has been reported before. This study evaluated the anticancer and immunomodulatory efficacy of PRO, PRE, PRO+PRE (PRO/PRE) and combination with melatonin (PRO+PRE+MEL) in a rat model, when breast cancer was induced by a direct-acting carcinogen N-nitroso-N-methylurea (NMU). MATERIALS AND METHODS: Daily administration of PRO (at a dose of 8.4×10(8) colony-forming units (c.f.u.)/rat), PRE (in the diet, 20 g/kg) and MEL (in tap water, 20 mg/l) started 14 days before the first NMU dose and lasted for 16 weeks. RESULTS: Although tumor growth was not altered, a marked decrease in the ratio of high-/low-grade carcinomas and in tumoral Ki-67 expression was found after PRO+PRE treatment; melatonin augmented these effects. PRO+PRE+MEL combination enhanced CD4(+) and CD8(+) T-cell tumor infiltration induced by PRO/PRE and increased CD25(+)FoxP3(+) regulatory T-cells in tumors. CONCLUSION: In mammary carcinogenesis, Lactobacillus plantarum LS/07 and inulin exert prodifferentiating, antiproliferative and immunomodulatory activities, which are significantly amplified by melatonin co-administration.
Keywords: prebiotic; melatonin; potkani Sprague-Dawley; Rats, Sprague-Dawley; inulin; oligofructose-enriched inulin; Antineoplastic Agents; Transforming Growth Factor beta1; zvířata; Melatonin; Rats; imunologické faktory; protinádorové látky; transformující růstový faktor beta1; Immunologic Factors; Breast cancer; experimentální nádory mléčných žláz; probiotic; krysa rodu Rattus; Lactobacillus plantarum; ženské pohlaví; Inulin; Probiotics; interleukin-6; Animals; Mammary Neoplasms, Experimental; methylnitrosomočovina; N-nitroso-N-methylurea; Interleukin-6; Methylnitrosourea; probiotika; Female